Answer:
Step-by-step explanation:
√(6-a)^2+(-2-a)^2+(0-a)^2 = 10
36-12a+a^2+4+4a+a^2+a^2 =100
3a^2 -8a -60=0
(3a+10)(a-6)=0
a= -3/10 or 6
Use the figure to decide the type of angle pair that describes
<5 and <6
Answer:
corresponding angles
Step-by-step explanation:
Corresponding angles are in matching corners .
Both 5 and 6 are in the lower left corner
Given the functions f(x) = 2x + 5 and g(x) = x2 + 8, which of the following functions represents f(g(x)] correctly?
1. f[g(x)] = 4x2 + 20x + 32
2. f(g(x)] = 4x2 + 20x + 25
3. f[g(x)) = 2x2 + 16
4. f(g(x)) = 2x2 + 21
Answer:
Choice 4.
Step-by-step explanation:
f(g(x))
Replace g(x) with x^2+8 since g(x)=x^2+8.
f(g(x))
f(x^2+8)
Replace old input,x, in f with new input, (x^2+8).
f(g(x))
f(x^2+8)
2(x^2+8)+5
Distribute:
f(g(x))
f(x^2+8)
2(x^2+8)+5
2x^2+16+5
Combine like terms:
f(g(x))
f(x^2+8)
2(x^2+8)+5
2x^2+16+5
2x^2+21
Answer:
D
Step-by-step explanation:
Took the test
Helpppppo!!!!!!!!!
The mean of the temperatures in the chart is 24° with standard deviation of 4º. How many years had temperatures within one
standard deviation of the mean?
20
25
28
35
Answer:
25
Step-by-step explanation:
If the mean of the temperatures in the chart is 24° with standard deviation of 4º, there has been 25 years within one standard deviation of the mean.
27° is the temperature value that is within one standard deviation of mean.
What is Mean?Mean is the average of the given numbers and is calculated by dividing the sum of given numbers by the total number of numbers.
Given
Mean of the temperatures in the chart [tex]\mu[/tex] [tex]\mew[/tex]= 24°
Standard deviation [tex]\sigma[/tex] = 4º
The lower and upper bound for temperature within one standard deviation of the mean is given as:
Lower bound = [tex]\mu[/tex] - [tex]\sigma[/tex] = 24° - 4º = 20°
Thus, the lower bound is = 20°
Upper bound = [tex]\mu[/tex] + [tex]\sigma[/tex] = 24° + 4º = 28°
Thus, the upper bound is = 28°
Now, the temperature value between (Lower bound, Upper bound) that is (20°, 28°) is said to be within one standard deviation of the mean.
Hence, 27° is the temperature value that is within one standard deviation of mean.
Find out more information about mean here
brainly.com/question/13000783
#SPJ2
Find the reference angle given: t = -216º.
Answer:
Step-by-step explanation:
To find the reference angle for an angle given in degrees, you can follow these steps:
Determine the absolute value of the given angle.
If the angle is more significant than 360 degrees, subtract the largest possible multiple of 360 degrees to bring it within the range of 0 to 360 degrees.
If the angle is negative, convert it to a positive angle by adding 360 degrees.
The reference angle is the acute angle formed between the terminal side of the angle and the x-axis.
Let's apply these steps to the given angle t = -216 degrees:
Absolute value of -216: | -216 | = 216 degrees
216 degrees is already within the 0 to 360-degree ranges, so there is no need to subtract any multiple of 360 degrees.
Since the angle is negative, convert it to a positive angle: 216 degrees
The reference angle is the acute angle formed with the terminal side of the angle, which is 216 degrees.
Therefore, the reference angle for t = -216 degrees is 216 degrees.
What is the solution to the system of equations below when graphed?
y=3x+1
y=4x-1
A. (3,4)
B. (1,-1)
C. (6,8)
D. (2,7)
Answer:
A
Step-by-step explanation:
Lets say x=1
y: 3(1)+1=4
x: 4(1)-1=3
Final answer:
The correct option is (D) (2,7). To solve the system of equations, set them equal to each other and solve for x, which is 2, and then substitute x back into either equation to find y, which is 7. Hence, the intersection point is (2, 7).
Explanation:
To find the solution to a system of equations when graphed, you look for the point where the two lines intersect. The given equations are y=3x+1 and y=4x-1.
Since both equations equal y, you can set them equal to each other to find the point of intersection:
3x + 1 = 4x - 1.
To solve for x, subtract 3x from both sides:
1 = x - 1.
Then, add 1 to both sides to isolate x:
x = 2.
To find the corresponding y value, substitute x into one of the original equations, let's use the first one:
y = 3(2) + 1,
which simplifies to y = 6 + 1 = 7.
Therefore, the solution to the system of equations and the point of intersection is (2, 7).
ces
Question 8 of 20 :
Select the best answer for the question
8. Gina decided to order some clothes from a catalogue. She ordered 3 pairs of jeans at $39 each, 4 T-shirts at $15 each, and 2 skirts at
$27 each. What was her total bill?
A. $192
B. $231
C. $117
D. $177
(1 point) Solve the equation in the interval [0,2π]. If there is more than one solution write them separated by commas. (sin(x))2=1/36
To solve (sin(x))^2 = 1/36, we find the arcsine of ±1/6. The solutions are sin⁻¹(1/6), π - sin⁻¹(1/6), 2π - sin⁻¹(1/6), and π + sin⁻¹(1/6) within the interval [0,2π].
Explanation:To solve the equation (sin(x))^2 = 1/36 in the interval [0,2π], we first take the square root of both sides to get sin(x) = ±1/6. The sine function oscillates between -1 and 1 every 2π radians, which means that we are looking for angles where the sine value is ±1/6.
To find the specific angles, we use the arcsine function or inverse sine function. The principal value of sin⁻¹(1/6) gives us one of the solutions, and considering the symmetry of the sine function, the other solutions can be found in the second and fourth quadrants, where the sine function is positive and negative, respectively.
The solutions to sin(x) = 1/6 in the interval [0,2π] are x = sin⁻¹(1/6) and x = π - sin⁻¹(1/6). For sin(x) = -1/6, the solutions are x = 2π - sin⁻¹(1/6) and x = π + sin⁻¹(1/6). Thus, the solutions to the original equation (sin(x))^2 = 1/36 within [0,2π] are sin⁻¹(1/6), π - sin⁻¹(1/6), 2π - sin⁻¹(1/6), and π + sin⁻¹(1/6), all of which can be calculated to find the exact values.
What is the solution to the linear equation?
4b + 6 = 2 - 6 + 4
Answer:
-1½ = b
Step-by-step explanation:
Combining all like-terms on the right side of the equivalence symbol will give you this:
4b + 6 = 0
- 6 -6
------------
4b = -6 [Divide by 4]
b = -1½ [OR -1,5]
I am joyous to assist you anytime.
The lengths of two sides of a right triangle are 5 inches and 8 inches. What is the difference between the two possible
lengths of the third side of the triangle? Round your answer to the nearest tenth.
3.1 inches
3.2 inches
10.0 inches
15.7 inches
Answer:
Option 2 - 3.2 inches.
Step-by-step explanation:
Given : The lengths of two sides of a right triangle are 5 inches and 8 inches.
To find : What is the difference between the two possible lengths of the third side of the triangle?
Solution :
According to question, it is a right angle triangle
Applying Pythagoras theorem,
[tex]H^2=P^2+B^2[/tex]
Where, H is the hypotenuse the longer side of the triangle
P is the perpendicular
B is the base
Assume that H=8 inches and B = 5 inches
Substitute the value in the formula,
[tex]8^2=P^2+5^2[/tex]
[tex]64=P^2+25[/tex]
[tex]P^2=64-25[/tex]
[tex]P^2=39[/tex]
[tex]P=\sqrt{39}[/tex]
[tex]P=6.24[/tex]
Assume that P=8 inches and B = 5 inches
Substitute the value in the formula,
[tex]H^2=8^2+5^2[/tex]
[tex]H^2=64+25[/tex]
[tex]H^2=89[/tex]
[tex]H=\sqrt{89}[/tex]
[tex]H=9.43[/tex]
Therefore, The possible length of the third side of the triangle is
[tex]L=H-P[/tex]
[tex]L=9.43-6.24[/tex]
[tex]L=3.19[/tex]
Therefore, The difference between the two possible lengths of the third side of the triangle is 3.2 inches.
So, Option 2 is correct.
The difference between the two possible lengths of the third side, rounded to the nearest tenth, is:
B. 3.2 inches
To determine the difference between the two possible lengths of the third side of a right triangle with given side lengths of 5 inches and 8 inches, we need to consider both cases where the unknown side could be the hypotenuse or one of the legs. We use the Pythagorean theorem, [tex]\(a^2 + b^2 = c^2\)[/tex].
Case 1: The unknown side is the hypotenuse [tex](\(c\))[/tex]
[tex]\[ c = \sqrt{5^2 + 8^2} = \sqrt{25 + 64} = \sqrt{89} \approx 9.4 \, \text{inches} \][/tex]
Case 2: The unknown side is one of the legs [tex](\(a\) or \(b\))[/tex]
Assume the known hypotenuse is 8 inches. Using the Pythagorean theorem, we solve for the other leg.
[tex]\[ 8^2 = 5^2 + x^2 \][/tex]
[tex]\[ 64 = 25 + x^2 \][/tex]
[tex]\[ x^2 = 64 - 25 \][/tex]
[tex]\[ x^2 = 39 \][/tex]
[tex]\[ x = \sqrt{39} \approx 6.2 \, \text{inches} \][/tex]
Difference between the two possible lengths
The two possible lengths of the third side are approximately 9.4 inches and 6.2 inches. The difference between these lengths is:
[tex]\[ 9.4 - 6.2 = 3.2 \][/tex]
Therefore, the difference between the two possible lengths of the third side, rounded to the nearest tenth, is:
B. 3.2 inches
The correct question is:
The lengths of two sides of a right triangle are 5 inches and 8 inches. What is the difference between the two possible
lengths of the third side of the triangle? Round your answer to the nearest tenth.
A. 3.1 inches
B. 3.2 inches
C. 10.0 inches
D. 15.7 inches
what is the answer for 2a x -a?
Answer:
-2a²
Step-by-step explanation:
The question is 2a × -a
This means 2a(-a)
= -2×(a×a)
=-2(a²)
=-2a²
place parenthesis in the expression below to make it a true statement.
5+5÷5X5=0
30 POINTS! Consider the system of linear equations and the matrix equations below.
What is the value of x in the equation?
Answer:
Option C is correct.
Step-by-step explanation:
-x+3y=2
4x-2y=22
In matrix form is represented as:
[tex]\left[\begin{array}{cc}-1&3\\4&-2\end{array}\right] \left[\begin{array}{c}x&y\end{array}\right] =\left[\begin{array}{c}2&22\end{array}\right][/tex]
AX=B
[tex]X = A^{-1}B[/tex]
[tex]A^{-1} = |A|/Adj A[/tex]
|A| = (-1)(-2)-(3)(4)
|A| = 2-12
|A| = -10
Adj A = [tex]\left[\begin{array}{cc}-2&-3\\-4&-1\end{array}\right][/tex]
A^-1 = -1/10[tex]\left[\begin{array}{cc}-2&-3\\-4&-1\end{array}\right][/tex]
A^-1 = 1/10[tex]\left[\begin{array}{cc}2&3\\4&1\end{array}\right][/tex]
X= A^-1 B
X = 1/10[tex]\left[\begin{array}{cc}2&3\\4&1\end{array}\right][/tex][tex]\left[\begin{array}{c}2&22\end{array}\right][/tex]
X=1/10[tex]X=1/10\left[\begin{array}{c}2*2+3*22\\4*2+1*22\end{array}\right]\\X=1/10\left[\begin{array}{c}4+66\\8+22\end{array}\right]\\X=1/10\left[\begin{array}{c}70\\30\end{array}\right]\\X=\left[\begin{array}{c}70/10\\30/10\end{array}\right]\\X=\left[\begin{array}{c}7\\3\end{array}\right][/tex]
So, x = 7 and y =3
Hence Option C is correct.
Answer:
7
Step-by-step explanation:
right on edge
write an inequality to represent the graph?
[tex]y > \frac{2}{5}x - 3 [/tex]
[tex]y < \frac{2}{5}x - 3[/tex]
[tex]y > \frac{5}{2}x - 3[/tex]
[tex]y < \frac{5}{2}x - 3[/tex]
which one is it 1,2,3,or 4 one
Answer:
[tex]\large\boxed{y>\dfrac{5}{2}x-3}[/tex]
Step-by-step explanation:
<, > - dotted line
≤, ≥ - solid line
<, ≤ - shaded region below the line
>, ≥ - shaded region above the line
We have dotted line (<, >) and shaded region above the line (>, ≥).
Therefore your answer is:
[tex]y>\dfrac{2}{5}x-3[/tex] or [tex]y>\dfrac{5}{2}x-3[/tex]
Calculate the slope.
The formula of a slope:
[tex]m=\dfrac{y_2-y_1}{x_2-x_1}[/tex]
Put the coordinates of the given points from the graph:
(0, -3) and (2, 2):
[tex]m=\dfrac{2-(-3)}{2-0}=\dfrac{5}{2}[/tex]
A customer cash a 1000.00 check at 3 percent how much does he receive back?
Let r = amount customer gets back
r = 1000 - (1000)(0.03)
r = 1000 - 30
r = $970
what is 240,567 divided by 67 is 3590
Answer:
Step-by-step explanation:
_____
Good evening ,
_______________
Look at the photo below for the answer.
___
:)
Mrs Richards buys 8 quarts of milk in 4 days .How many gallons of milk does she buy?
Answer: 2 gallons
Step-by-step explanation:
1 gallon = 4 quarts
8 divided by 4= 2
perform the indicated operation 1 1/3 × 3 3/4
Answer:
5.
Step-by-step explanation:
1 1/3 * 3 3/4
= 4/3 * 15/4
= 60/12
= 5.
First we simplify,
[tex]1\dfrac{1}{3}\cdot3\dfrac{3}{4}[/tex]
to
[tex]\dfrac{4}{3}\cdot\dfrac{15}{4}[/tex]
Then we continue simplifying,
[tex]
\dfrac{4\cdot15}{4\cdot3}=\dfrac{15}{3}=\boxed{5}
[/tex]
Hope this helps.
r3t40
What is the area of a rectangle with a length of 27 and a height of 56?
Answer:
A=1512
Step-by-step explanation:
The area of a rectangle with a length of 27 and a height of 56 is 1512.
Formula: A=wl
A=wl=56·27=1512
Answer: 1,512 units^2
Step-by-step explanation: To find the area of a rectangle, multiply the length by the width. 27 x 56 =1512. Since you are finding the area, the answer would be squared.
Determine what type of model best fits the given situation: A $500 raise in salary each year.
Answer:
A linear modelExplanation:
The type of model that best fits the situation of a $500 raise in a salary each year is a linear model.
In a linear model, the dependent variable changes a constant amount for constant increments of the independent variable.
In the given case, the dependent variable is the salary and the independent variable is the year.
You may build a table to show that for increments of 1 year the increments of the salary is $500:
Year Salary Change in year Change in salary
2010 A - -
2011 A + 500 2011 - 2010 = 1 A + 500 - 500 = 500
2012 A + 1,000 2012 - 2011 = 1 A + 1,000 - (A + 500) = 500
So, you can see that every year the salary increases the same amount ($500).
In general, a linear model is represented by the general equation y = mx + b, where x is the change of y per unit change of x, and b is the initial value (y-intercept).
In this case m = $500 and b is the starting salary: y = 500x + b.
Drag steps in the given order to evaluate this expression. -3(-3+2)-6
Answer:
The answer is -3.
Step-by-step explanation:
-3(-3+2)-6
First solve the parenthesis. -3+2= -1.
-3(-1)-6
-3 times -1 is 3. Two negatives always equal a positive.
3-6 = -3.
In the pendulum formula, we use g=9.8 m/s^2 for the acceleration due to gravity on Earth. But what about on Venus? If an astronaut on the surface of Venus swings a 1-meter long pendulum, and it has a period of 2.11 seconds, what is the acceleration due to gravity, g, on Venus?
Answer:
Option A is the correct answer.
Step-by-step explanation:
Period of simple pendulum is given by the expression,
[tex]T=2\pi \sqrt{\frac{l}{g}}[/tex]
Where l is the length of pendulum, g is acceleration due to gravity.
Here given for Venus
Period, T = 2.11 s
Length of pendulum, l = 1 m
We need to find acceleration due to gravity, g
Substituting
[tex]2.11=2\pi \sqrt{\frac{1}{g}}\\\\\sqrt{g}=\frac{2\pi}{2.11}\\\\g=8.87m/s^2[/tex]
Acceleration due to gravity of Venus = 8.9 m/s²
Option A is the correct answer.
Help on 10 and 11 and give me the answers for the blank ones
Answer:
10) Exact Answer: 36
Estimate: 36
11) Exact Answer: 2001
Estimate: 1900
Step-by-step explanation:
10a) To find the exact answer, simply divide the given numbers.
10b) To find the estimated answer, use compatible numbers. We know that any "hundred" number is easily divisible by 5. Therefore, 900/5 = 36.
It is possible for the estimate to be the same as the exact answer.
10a) To find the exact answer, simply divide the given numbers.
10b) To find the estimated answer, use compatible numbers. There is no pattern we can look for, so round to the nearest whole number.
We know that if we rounded .38 to 0 or 1, the answer would not be nearly as close as if we rounded .38 to .4.
Therefore, 760/.4 = 1900
Please mark as Brainliest, hope this helps!
Volume of prisms, but what is this?
Answer:
left 29226 Right 134
Step-by-step explanation:
volume=base*height
(22*22+(11)^2 *3.14*3/4)*38=29226
((1.4+0.6)*2*0.7+1.4*2*1.4+0.6*1.4+0.6*1.4))* 16=134
Answer:
29,225.78 m^3 to the nearest hundredth.
134.4 m^3.
Step-by-step explanation:
The building:
The area of the floor = area of the square + 3/4 * area of the circle
= 22^2 + 3/4 π 11^2.
The volume of the building =
38 * (22^2 + 3/4 π 11^2)
= 29,225.78 m^3.
The greenhouse:
The sides consist of 2 pairs of trapezoids.
Area of a side = 2 * (0.6/2)(0.7 + 2.1) + 2 * (1.4/2)(2.1 + 2.7)
The length is 16 m so:
Volume = 16 * [ 2 * (0.6/2)(0.7 + 2.1) + 2 * (1.4/2)(2.1 + 2.7) ]
= 134.4 m^3.
What is the product?
(4y - 3)(2y2 + 3y – 5)
8y3 + 3y + 15
8y3 – 23y + 15
8y3 - 6y2 - 17y + 15
O 8y2 + 6y2 - 29y + 15
Answer:
8y³ + 6y² - 29y + 15
Step-by-step explanation:
Take each separate term in the second set of parentheses and multiply it by the terms in the first set of parentheses. Put them altogether, and you will arrive at the above answer.
I am joyous to assist you anytime.
Hence, the product is [tex]8y^3+6y^2-29y+15[/tex]
What is product?The product of two numbers is the result you get when you multiply them together. So 12 is the product of 3 and 4, 20 is the product of 4 and 5, and so on.
How to solve?multiplying corresponding terms,
[tex](4y-3)(2y^2+3y-5)\\8y^3+12y^2-20y-6y^2-9y+15\\8y^3+6y^2-29y+15[/tex]
Hence, the product is [tex]8y^3+6y^2-29y+15[/tex]
to learn more about product: https://brainly.com/question/1755985
#SPJ2
PLEASE DO 41 AND 45!!!!!!
Answer:
see below
Step-by-step explanation:
41
-4 ≤2+4x<0
Subtract 2 from all sides
-4-2 ≤2-2+4x<0-2
-4 ≤2+4x<0
Divide all sides by 4
-6/4 ≤4x/4<-2/4
-3/2 ≤x <-1/2
graph is attached
45
2x-3 ≤-4 or 3x+1 ≥4
Lets solve the left side first
2x-3≤-4
Add 3 to each side
2x-3+3 ≤-4+3
2x ≤-1
Divide by 2
2x/2 ≤-1/2
x ≤-1/2
Now solve the right inequality
3x+1 ≥4
Subtract 1 from each side
3x+1-1 ≥4-1
3x ≥3
Divide by 3
3x/3 ≥3/3
x≥1
So we have
x ≤-1/2 or x≥1
see attached
Notice closed circles where there is a greater than equal to or less than equal to
is 36a^2-9 a difference of squares? a. yes b. no
Answer:
yes
Step-by-step explanation:
The difference of squares is x^2 - y^2 = (x-y) (x+y)
36a^2 = (6a)^2
9 = (3)^2
(6a -3) (6a+3)
This is the difference of squares
The correct answer is a. Yes, 36a² - 9 is a difference of squares
The given expression is [tex]36a^2 - 9[/tex].
To determine if it is a difference of squares we need to identify if it can be written in the form of a² - b², which factorizes to (a + b)(a - b).
We can see that
36a² is a perfect square because it can be written as (6a)² and 9 is also a perfect square because it can be written as 3². Therefore, we can rewrite the expression as:
[tex]36a^2 - 9 = (6a)^2 - 3^2[/tex]
Thus, we can see that the expression 36a² - 9 is a difference of 6a square and 3 square. So, it is indeed a difference of squares.
Answer: a. Yes, 36a² - 9 is a difference of squares
The price of an iPod dropped from $210.95 to $165.88.
What was the percent decrease in prices? (round to the
nearest hundredth)
o 21.37%
o 21.34%
O 21.38%
O none of the above
Answer:
The correct answer would be option A, 21.37
Step-by-step explanation:
In order to find out the percentage change of price of a product, either increase of decrease, that is found by finding the change in the price and then divide it by the base price and then finding the percentage of that price. The whole process is as follows:
Original price of iPod: $210.95
New Price of iPod: $165.88
Decrease in the price of iPod: 210.95-165.88= 45.07
Now dividing decreased price with the original price we get:
45.07/210.95=0.213652
Now to find the percentage, we need to multiply it with 100
0.213652*100=21.3652% which is approximately 21.37%
Find the complete factored form of the polynomial -24a6b4-40a3
For this case we have the following polynomial:
[tex]-24a ^ 6b ^ 4-40a ^ 3[/tex]
We must find the greatest common factor of the terms of the polynomial.
The GCF of the coefficients is given by:
[tex]24 = 3 * 8\\40 = 5 * 8[/tex]
Then we look for the GFC of the variables:
We have then:
[tex]a ^ 6 = a ^ 3a ^ 3\\a ^ 3 = a ^ 3[/tex]
Finally rewriting we have: [tex]-24a ^ 6b ^ 4-40a ^ 3 = -8a ^ 3 (3a ^ 3b ^ 4 + 5)[/tex]
Answer:
the complete factored form of the polynomial is:
[tex]-8a ^ 3 (3a ^ 3b ^ 4 + 5)[/tex]
Which statements accurately describe the function f(x) = 3 sqrt 18?
algebra II engenuity
Answer:
The statements which accurately describe f(x) are
The domain is all real numbers ⇒ 1st answer
The initial value of 3 ⇒ 3rd answer
The simplified base is 3√2 ⇒ last answer
Step-by-step explanation:
* Lets explain how to solve the problem
- The form of the exponential function is f(x) = a(b)^x, where a is the
initial value , b is the base and x is the exponent
- The values of a and b are constant
- The domain of the function is the values of x which make the function
defined
- The range of the function is the set of values of y that correspond
with the domain
* Lets solve the problem
∵ [tex]f(x)=3(\sqrt{18}) ^{x}[/tex]
- The simplest form of is :
∵ √18 = √(9 × 2) = √9 × √2
∵ √9 = 3
∴ √18 = 3√2
∴ [tex]f(x)=3(3\sqrt{2})^{x}[/tex]
∵ [tex]f(x)=a(b)^{x}[/tex]
∴ a = 3 , b = 3√2
∴ The initial value is 3
∴ The simplified base is 3√2
- The exponent x can be any number
∴ The domain of the function is x = (-∞ , ∞) or {x : x ∈ R}
- There is no value of x makes y = 0 or negative number
∴ The range is y = (0 , ∞) or {y : y > 0}
* Lets find the statements which accurately describe f(x)
# The domain is all real numbers
∵ The domain is {x : x ∈ R}
∴ The domain is all real numbers
# The initial value is 3
∵ a = 3
∵ a is the initial value
∴ The initial value of 3
# The simplified base is 3√2
∵ b = √18
∵ b is the base
∵ The simplified of √18 is 3√2
∴ The simplified base is 3√2
- For more understand look to the attached graph
y = – x – 6 y = x – 4 solve the system of equations using substition. HELP NEEDED IMMEDITLY!!!!!!!!
Answer:
x=-1 y= -5
Step-by-step explanation:
y = – x – 6
y = x – 4
Substitute into y = -x-6 into the second equation
y =x-4
-x-6 = x-4
Add x to each side
-x-6+x =x-4+x
-6 =2x-4
Add 4 to each side
-6+4 =2x-4+4
-2 = 2x
Divide by 2
-2/2 =2x/2
-1 = x
Now find y
y =-x-6
y = -(-1) -6
y =1-6
y = -5
Answer:
x = -1
y = -5
Step-by-step explanation:
Given:
y = – x – 6 y = x – 4We'd take one of the equations above and substitute it with the y variable:
x - 4 = -x - 6
-x is smaller, so we add x in both sides:
2x - 4 = -6
Add 4 in both sides:
2x = -2
Divide 2 in both sides:
x = -1
Solve for y
y -(-1) - 6 = -5
y = -5
Our answer is x = -1, y = -5